Implementation of Public Policy at The Local Level: A Study of The Ban on The Distribution and Sale of Alcoholic Beverages - Robby Noor Ilham Hendriawan; Siti Khumayah; Leni Rohida (Jurnal Polisci, 2026)
Background. The distribution and sale of alcohol are issues that have a significant impact on social, health, and community safety factors. To address this problem, the Cirebon City Government issued Local Regulation No. 4 of 2013, which prohibits the distribution and sale of alcoholic beverages pursuant to Article 3. Alcoholic beverages are classified into three categories based on their ethanol (C₂H₅OH) content: Category A with an ethanol concentration of more than 1% to 5%, Category B with an ethanol concentration of more than 5% to 20%, and Category C with the highest ethanol concentration, namely more than 20% to 55%; and other alcoholic beverages. Aims. The study aims to analyze the implementation and policy factors of the ban on the distribution and sale of alcoholic beverages, ranging from aspects of communication, resources, disposition, to bureaucratic structure, so as to provide a comprehensive overview and input for strengthening public policy in accordance with Local Regulation No. 4 of 2013, Article 3. Methods. This study employs a qualitative, descriptive approach. This study employs the implementation theory proposed by George C. Edwards III (Subianto, 2020:12). Result. The findings indicate that the dimensions of Disposition and Bureaucratic Structure have been effectively implemented, as evidenced by the high level of commitment among law enforcement officials and the execution of duties in accordance with Standard Operating Procedures (SOPs). However, the policy's effectiveness is still hampered by issues in the Communication and Resources dimensions, particularly uneven information dissemination across all segments of society, as well as limited personnel and operational support equipment. Conclusion. The study identified the primary constraints as a shortage of human resources and limited time available for enforcement operations.